Consolidation Strategies for Enhancing Stability of Indonesian Islamic Regional Banks: Merger versus Joint Business Groups - Anita Permanasari; M. Nur Rianto Al Arif; Muhamad Nadratuzzaman Hosen; Titi Dewi Warninda (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
A strategic option to accelerate core capital fulfilment and the conversion of sharia business units into full-fledged sharia commercial banks is consolidation through mergers and joint business groups. This approach is particularly relevant for sharia business units under regional development banks that occupy the defensive quadrant in terms of competitiveness and financial performance. This study develops an empirical model to evaluate the influence of internal and external factors on the stability of UUS BPD and to simulate potential resilience gains post-consolidation. Using panel data from 12 UUS BPD between Q1 2012 and Q4 2022, the research applies cluster analysis, the fixed effect model, the analytic hierarchy process, and merger simulation. Results reveal that consolidation supported by profitability, asset growth, and sound risk management significantly improves financial stability. Merger simulations yield Z-scores of 1.1–2.6, indicating moderate stability, while the joint business groups simulation with BJB Syariah shows steady improvement from baseline. Consolidation serves not only as a growth strategy but also as a survival mechanism for Sharia Business Units BPDs facing regulatory and structural challenges, with both merger and Joint Business Groups options classified as moderately prospective for post-consolidation sustainability.